CONTEXTUAL FACTORS ASSOCIATED WITH TEENAGE PREGNANCY AND CHILDBEARING IN NIGERIA - KUPOLUYI, J. A.; Hurricane-Ike, E. O.; OYINLOYE, B. O. (IJRDO - Journal of Social Science and Humanities Research, 2016)
Background: Teenage pregnancy and childbearing seem to be continuing unabated in Nigeria despite efforts to reduce the rates.Objective: This study examined the individual and community-level factors associated with teenage pregnancy and childbearing in Nigeria.